Bilateral lung metastases unveils an asymptomatic sacrococcygeal yolk sac tumor - Krishnendu Mondal; Rupali Mandal (Wolters Kluwer Medknow Publications, 2017)
Sacrococcygeal yolk sac tumor is an uncommon pediatric neoplasm. It usually presents with intra-abdominal or gluteal pain and mass. At later stage, it disseminates to regional nodes and distant organs. We describe one such neoplasm in an 18-month-old male child who turned symptomatic with multiple bilateral lung metastases. The tumor produced the least deformity to his physique, to become detectable on routine inspection and clinical examination. Finally, a combined approach through clinical, radiological, pathological, and biochemical perspectives established the diagnosis.